Carboplatin-containing regimens as front-line treatment for advanced non-small-cell lung cancer in two groups of elderly. (April 2014) - Giuliani, Jacopo; Piacentini, Paolo; Greco, Filippo; Mercanti, Anna; Trolese, Anna Rita; Furini, Lara; Durante, Emilia; Moratello, Giacomo; Tognetto, Michele; Bonetti, Andrea
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: We evaluated the impact of a carboplatin-based doublet in two groups of elderly patients with advanced non-small cell lung cancers (NSCLC). Materials and Methods: A retrospective analysis of all consecutive elderly patients (≧70 year old) with advanced NSCLC who received a carboplatin-based doublet as front-line therapy at our medical oncology unit was performed. Results: In the study, 57 consecutive elderly patients with advanced NSCLC were included. Carboplatin was combined with vinorelbine in 41 patients (71·9%) and with gemcitabine in 16 patients (28·1%). Overall, a total of 227 cycles were administered to 57 patients – 142 cycles were administered to patients in group 1 and 85 cycles were given to patients in group 2 – median number of administered cycles per patient was 4 (range 1–6). Of the patients, 35 (62%, group 1) were 'young-old' (70–74-year old) and 20 (38%, group 2) were 'old-old' (75–82-year old). Toxicity was mild in both subgroups (grade 3–4 neutropenia in 17·1% of group 1 and in 9·1% of group 2). At the univariate analysis, the median overall survival (OS) was 10·07 months (P = 0·789, 95% CI: 8·49–11·64), 10·1 months in group 1 and 9·8 months in group 2. Conclusions: This evaluation shows the safety and efficacy of a carboplatin-based doublet given as first-line chemotherapy in elderly advanced NSCLC patients. The combination with vinorelbine or gemcitabine is associated with a very good toxicity profile that does not seem to have a detrimental effect on efficacy.